2019
DOI: 10.3389/fnagi.2019.00019
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Perfusion and Cerebrovascular Reactivity in Elderly Controls With Subtle Cognitive Deficits

Abstract: Background: Recent studies suggested that arterial spin labeling (ASL)-based measures of cerebral blood flow (CBF) as well as cerebral vasoreactivity to CO 2 (CVR CO 2 ) show significant alterations mainly in posterior neocortical areas both in mild cognitive impairment (MCI) and Alzheimer disease. It remains, however, unknown whether similar changes occur in at risk healthy elders without clinically overt symptoms. This longitudinal study investigated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Correlation is significant at the 0.05 level (two-tailed).CBF[38]. van der Thiel et al[39] and De Vis et al[40] demonstrated that local and global CBF were predictive of cognition among elderly patients during follow-up. Finally, Cecchetti et al found that brain hemodynamicFigure 1.…”
mentioning
confidence: 98%
“…Correlation is significant at the 0.05 level (two-tailed).CBF[38]. van der Thiel et al[39] and De Vis et al[40] demonstrated that local and global CBF were predictive of cognition among elderly patients during follow-up. Finally, Cecchetti et al found that brain hemodynamicFigure 1.…”
mentioning
confidence: 98%
“…Moreover, previous studies confirmed a negative association between volume of WMHs and CBF values in the orbital frontal region ( 47 ). Of note, the results showed that both the hypoperfusion and hyperperfusion areas existed and we found that hyperperfusion in the IFG.L (triangular part) region was presented in WMHs, which was possibly attributable to neuronal adaptive responses and compensatory mechanisms in very early pathological processes to maintain cognitive function that actually reflect dysregulation of the neurovascular unit (NVU) ( 48 ). The hypoperfusion and hyperperfusion areas may simultaneously involve different brain regions and the asymmetrical results in this study may be due to the dominant left hemisphere being more often associated with various advanced cognitive functions ( 49 ).…”
Section: Discussionmentioning
confidence: 86%
“…Other human studies have indicated that hyperoxia induces cerebral vasoconstriction as a consequence of altered regional nitric oxide potentially contributing to the stress diathesis under anaesthesia. 44 Also of note are findings of altered CVR with increasing age 45 and with signs of dementia in the elderly 46 or in patients with biomarkers such as APO4ε related to early onset Alzheimer's disease. 47 The identification of regional 'intracranial steal' or 'blue brain' on the BOLD images with a CO2 ramp protocol is increasingly being used to establish the need for and measure results from revascularization with superficial temporal artery to middle cerebral artery (STA-MCA) anastomoses in patients with severe intracranial vascular compromise.…”
Section: Discussionmentioning
confidence: 99%